Resilience, illness perception of disease, beliefs and spiritual-religious coping in relation to the health-related quality of life in chronic colombian patients. - Vinaccia, Steffano; Quiceno, Japcy Margarita; Remor, Eduardo (Anales de Psicología / Annals of Psychology, 2012)
The aim of this study was to evaluate the resilience, illness perception, beliefs and spiritual-religious coping above health-related quality of life in 121 patients from Medellin (Colombia) with chronic kidney disease (n = 40), rheumatoid arthritis (n = 41) and chronic obstructive pulmonary disease (n = 40). Instruments: resilience scale RS, the Connor-Davidson resilience scale CD-RISC2, the brief illness perception questionnaire IPQ-B, systems of beliefs inventory SBI-15R, spiritual coping scale SCS and medical outcomes study short form 36 ítems MOS SF-36. The results of multiple linear regression analysis indicated that the consequences and emotional response of illness perception had a negative weight on the mental health index, and personal competence -RS, years of study and non-religious coping had a positive weight. And the consequences -IPQ-B, age and time of diagnosis of the disease had a negative weight above physical health index. Conclusion, HRQOL is more affected by the consequences, while that the years of schooling, more diagnosis time and years older favor it. Finally beliefs/practices and the spiritual-religious coping are not significant above HRQL.